2008
DOI: 10.1021/es801481s
|View full text |Cite
|
Sign up to set email alerts
|

Treatability of U.S. Environmental Protection Agency Contaminant Candidate List Viruses: Removal of Coxsackievirus and Echovirus using Enhanced Coagulation

Abstract: Enhanced coagulation was evaluated for removal efficacy of coxsackievirus and echovirus (Contaminant Candidate List [CCL] enteroviruses), poliovirus, four potential surrogate bacteriophages, and dissolved organic carbon (DOC). Viruses and DOC were effectively removed using enhanced coagulation, with removals generally improving as dose increased and pH decreased. Optimal enhanced coagulation conditions of 40 mg/L FeCl3 and pH between 5 and 6.5 resulted in a maximum removal of 3.0 logs of coxsackievirus B6, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 22 publications
1
44
0
2
Order By: Relevance
“…The physical removal of coxsackievirus and echovirus (Mayer et al 2008) and adenovirus ) using enhanced coagulation was presented in the companion studies. Here, the removal efficacy of C. parvum oocysts is described.…”
Section: Oocyst Removal By Enhanced Coagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical removal of coxsackievirus and echovirus (Mayer et al 2008) and adenovirus ) using enhanced coagulation was presented in the companion studies. Here, the removal efficacy of C. parvum oocysts is described.…”
Section: Oocyst Removal By Enhanced Coagulationmentioning
confidence: 99%
“…To date, there are limited data on the physical removal of CCL viruses during water treatment processes Abbaszadegan et al 2007Abbaszadegan et al , 2008Mayer et al 2008). One reason for this limitation is the practical difficulty of performing bench-or pilot-scale experiments for the removal studies of microbial pathogens, particularly in microbial detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…[25] This is about 50% reduction of its sensitivity to UV disinfection compared to the VSI of X174 (phage) that is cultured in the host cell of E. coli ATCC 13706, which may result from larger surface areas of X174 (phage) as shown in the electromicroscopic scanning image. [33] A cumulative plot shows that more than 95% of virus will be more sensitive than MS2-phage. Therefore, MS2-phage is a very conservative surrogate virus in regulating the performance of UV disinfection systems.…”
Section: Model Developmentmentioning
confidence: 99%
“…Although particle diameters and electrophoretic mobilities were almost the same for Qß and MS2 (Shirasaki et al 2009a), a marked difference in removal ratio was observed between total Qß and MS2. Abbaszadegan et al (2007) and Mayer et al (2008) reported that the removal ratio for MS2 was lower than that of adenoviruses, feline caliciviruses, coxsackieviruses, echoviruses and polioviruses by an enhanced coagulation process using ferrie chloride, and these researchers concluded that MS2 was an appropriate surrogate for enteric viruses. This difference was most likely the result of differences between the interactions of Qß and MS2 with the aluminium floe particles accumulated on the membrane surface as a cake layer.…”
Section: Total Bacteriophage Removal By the In-line Coagulationceramimentioning
confidence: 99%